University of Babylon Performance in Setting and Infrastructure Indicator through UIGreenMetric 2017-2020. (A comparative study) - Hussein, Kahtan H.; Hassoon, Abbas Fadhil; Abdulhassan, Aladdin; Al-Muttairi, Bushra MK.K.; Tameemi, Waleed A (Universitas Diponegoro, 2022)
The category of setting and infrastructure indicator (SI) is chosen in this comparative study referring to the fact file scores obtained by the University of Babylon during the last four participations into the UI Green Metric Rankings. In general, the scores indicated an escalation in the university performance of the whole six sub-indicators of the setting and infrastructure criterion (SI) from 2017-2020. These results confirmed that the university; by its leadership, staff and students, focused on upgrading and developing its infrastructure for setting a green and safe educational environment for most employees and students. That is to achieve a green campus contributing in the global efforts for achieving the UN agenda of SDGs 2015-2030. Furthermore, all practices of university performance coped with its vision, mission, and objective goals of university strategic plan from 2018-2022, which contained the commitments to set up with most of SDGs, especially related to sustainable cities or campuses. The results also showed an ascending and remarkable progress from 2017 to 2020 with an unexpected regression in 2019, which required the development of an improvement plan to address weaknesses, maintain and enhance strengths, to get good results for university in the 2020 edition of UI GreenMetric Ranking. Keyword: Green university, practices, Sustainable Development Goals (SDGs), SI, setting and infrastructure indicator, University of Babylon.